Deformation micro-mechanism for compression of magnesium alloys at room temperature analyzed by electron backscatter diffraction. (January 2015) - Song, G.S.; Chen, Q.Q.; Zhang, S.H.; Xu, Y.
Highlights: In-situ tracking on the evolution of grains orientation of magnesium alloy was carried out by EBSD. Distributions of twin bands were closely related to the activation of extension twin variants. Activation of extension twin significantly changes the order of Schmid factor of slips. Pyramidal slips become the dominant deformation mode at the late stage of compression. Abstract: In-situ tracking on the evolution of grains orientation of rolled magnesium alloy sheets compressed uniaxially at room temperature was carried out by the method of electron backscatter diffraction (EBSD), and meanwhile, distributions of twin bands, activations of twin and slips were also analyzed. The results show that the distributions of twin bands were closely related to the activation of extension twin variants. The activation of extension twin significantly changes the order of Schmid factor of different slips, and accordingly affects the activation of slips during the subsequent deformation.